Pengetahuan Pubertas Normal dan Siklus Menstruasi Remaja - C. Ermayani Putriyanti; Eka Ratnawati (JURNAL INFO KESEHATAN, 2019)
The degree of understanding of puberty is still very varied. It has an impact on the cleanliness of erroneous menstruation, which will have long-term effects on reproductive health. The study aims to identify adolescent knowledge about normal puberty and menstrual cycles. This research was a quantitative study of observational approach by using the knowledge survey of normal puberty and the menstrual cycle involving 55 students of State Junior High School (SMPN) 1 Parakan, Temanggung, Central Java. The technicality used descriptive statistics. The results of this study revealed that knowledge of the degree of normal paper and the menstrual cycle was still low (21.33%). The main sources of information about puberty and menstruation are thousands (85.5%). Teenagers do not know about the interval between the onset of puberty and menarche (87%), few adolescents understand the first sign of puberty (33%). Most teenagers have understood the normal menstrual cycle correctly (78%). There was no significant relationship between knowledge of the first sign of puberty with respondents' understanding of belief. Meanwhile, there was a significant relationship between menstrual status and knowledge about the menstrual cycle and the number of replacement pads. The results showed that students have a poor understanding of puberty, hence, health education must be given to students and their parents.